Practical, Evidence-Based Approaches to Nutritional Modifications to Reduce Atherosclerotic Cardiovascular Disease: An American Society For Preventive Cardiology Clinical Practice Statement - Danielle Belardo, MD; Erin D. Michos, MD, MHS, FASPC; Ron Blankstein, MD, FASPC; Roger S. Blumenthal, MD, FASPC; Keith C. Ferdinand, MD, FASPC; Kevin Hall, PhD; Kevin Klatt, PhD, RD; Pradeep Natajaran, MD, MMSc; Robert J. Ostfeld, MD, MSc; Koushik Reddy, MD; Renee Rodriguez, MD; Urshila Sriram, PhD, MSPH, RD; et al. (Elsevier, 2022)
Despite numerous advances in all areas of cardiovascular care, cardiovascular disease (CVD) is the leading cause of death in the United States (US). There is compelling evidence that interventions to improve diet are effective in cardiovascular disease prevention. This clinical practice statement emphasizes the importance of evidence-based dietary patterns in the prevention of atherosclerotic cardiovascular disease (ASCVD), and ASCVD risk factors, including hyperlipidemia, hypertension, diabetes, and obesity. A diet consisting predominantly of fruits, vegetables, legumes, nuts, seeds, plant protein and fatty fish is optimal for the prevention of ASCVD. Consuming more of these foods, while reducing consumption of foods with saturated fat, dietary cholesterol, salt, refined grain, and ultra-processed food intake are the common components of a healthful dietary pattern. Dietary recommendations for special populations including pediatrics, older persons, and nutrition and social determinants of health for ASCVD prevention are discussed.